How can vaccination prevent rabies in dogs? - International Livestock Research Institute (International Livestock Research Institute, 2022)
Rabies is a deadly disease in many parts of Africa. But it is entirely preventable through vaccination. Vaccination protects dogs and stops them from spreading the disease to other animals - or worse, to people. Epidemiological models have repeatedly shown that it is economically viable to vaccinate dogs rather than treating infected cases. A dog vaccination costs USD 2, while treating a human costs around USD 85.